Rezolvati in R ecuatiile
e) (2-√3) x =√3-2
f) (1-√7) x +√7-1=0
g) (2√10-1)x-(1-2√10)²=0
h) ( 5-√5)x=√5(√5-1)
Răspunsuri la întrebare
Răspuns de
1
e) (2-√3) x =√3-2
x=(√3-2)/(2-√3) =-(2-√3)/(2-√3)=-1
f) (1-√7) x +√7-1=0
x=(1-√7) /(1-√7) =1
g) (2√10-1)x-(1-2√10)²=0
x=(1-2√10)²/-(1-2√10)=-(1-2√10)=2√10-1
h) ( 5-√5)x=√5(√5-1)
x=√5(√5-1) /( 5-√5)=√5(√5-1)/√5(√5-1)=1
x=(√3-2)/(2-√3) =-(2-√3)/(2-√3)=-1
f) (1-√7) x +√7-1=0
x=(1-√7) /(1-√7) =1
g) (2√10-1)x-(1-2√10)²=0
x=(1-2√10)²/-(1-2√10)=-(1-2√10)=2√10-1
h) ( 5-√5)x=√5(√5-1)
x=√5(√5-1) /( 5-√5)=√5(√5-1)/√5(√5-1)=1
nechitamagdale:
Multumesc
Alte întrebări interesante
Matematică,
9 ani în urmă
Chimie,
9 ani în urmă
Franceza,
9 ani în urmă
Limba română,
10 ani în urmă
Matematică,
10 ani în urmă